The Role of Jargon in Wuthering Waves Discord Community: A Sociolinguistic Study - Hardi Suhardi (Jurnal Dieksis ID, 2026)
This study aims to analyze the forms of jargon and examine differences in jargon usage between casual players and lore seekers within the Wuthering Waves Discord community. The research adopts a descriptive qualitative approach, with data collected from 19 screenshots of Discord interactions that represent naturally occurring communication among community members. From these data, 24 jargon terms were identified as the primary focus of analysis. The collected data were examined using contextual interpretation to understand meaning in use, followed by classification based on linguistic form. The findings indicate that the jargon used in the community can be categorized into several forms, including single words, multi-word phrases, and abbreviations. Beyond form, the study also reveals clear variation in jargon usage based on player type. Casual players predominantly use jargon related to gameplay mechanics, character builds, strategies, and efficiency during play. In contrast, lore seekers tend to employ jargon associated with narrative elements, world-building concepts, and the game’s fictional universe. These findings demonstrate that jargon functions not only as a tool for efficient communication, but also as a reflection of players’ social roles, interests, and levels of engagement. Overall, this research contributes to a deeper understanding of language variation in online gaming communities and highlights the relationship between participation patterns and linguistic choice. This study shows that language variation in online gaming communities is shaped by participation patterns, revealing how engagement type and frequency influence players’ linguistic choices and reflect social interaction dynamics.